HUMAN PSYCHOLOGY (Центральноазиатский журнал образования и инноваций, 2025)
This article explores human psychology by analyzing its fundamental principles, theories, and practical applications in modern life. The study evaluates psychological behavior, cognition, and emotional responses to various stimuli. The research employs qualitative and quantitative methodologies to assess psychological traits and their impact on individuals. Special attention is given to cognitive psychology, behavioral psychology, and psychoanalysis. Statistical data and tabular analysis provide insights into psychological trends.